1985
DOI: 10.1063/1.335013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural effects of anelastic deformation of an amorphous alloy

Abstract: We present the first direct evidence of structural anisotropy due to anelastic polarization produced by mechanical creep, in the form of the anisotropic diffraction intensities observed by energy dispersive x-ray diffraction method. We suggest that this structural anisotropy is the origin of the creep-induced magnetic anisotropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 5 publications
2
43
0
Order By: Relevance
“…The origin of stress-induced anisotropy in amorphous materials is still not clear, although it is discussed in numerous publications [60][61][62]. The most common origin of stress-annealing-induced anisotropy is either "back stresses" or directional pair (chemical or topological) ordering [41][42][43][44][45][46][47][48][49][60][61][62]. Annealing:…”
Section: Resultsmentioning
confidence: 99%
“…The origin of stress-induced anisotropy in amorphous materials is still not clear, although it is discussed in numerous publications [60][61][62]. The most common origin of stress-annealing-induced anisotropy is either "back stresses" or directional pair (chemical or topological) ordering [41][42][43][44][45][46][47][48][49][60][61][62]. Annealing:…”
Section: Resultsmentioning
confidence: 99%
“…The stress-induced anisotropy of amorphous alloys annealed below crystallization temperatures (300-400°C) has been studied widely. 5,6 Himovich et al 6 studied the structural origin of the anisotropy by using energy dispersive x-ray diffraction. They observed the difference in intensities between the two diffraction vectors ͑parallel and perpendicular to the stress direction͒ and attributed it to the anisotropy in the angular distribution of the atomic bonds in the amorphous structure.…”
mentioning
confidence: 99%
“…Earlier studies [6,7] had shown that the creep induced anisotropy is due to the anisotropic bond reorientation, which produces anelastic polarization. The present M .…”
Section: Article In Pressmentioning
confidence: 98%
“…Extensive studies performed long ago in order to understand the atomic level origin of the induced anisotropy showed that for field-annealing the origin of this anisotropy is the well-known atomic pair ordering mechanism. In the case of annealing under stress, the latter induces structural anisotropy (directly observed in an energy dispersive X-ray experiment [6,7]), which is due to anelastic polarization produced by mechanical creep which causes that more atomic bonds become oriented perpendicular to the applied tensile stress [6,7]. Then, the magnetic anisotropy manifests itself by the dipolar or anisotropic exchange interactions.…”
Section: Introductionmentioning
confidence: 98%